BASELINE IMPLEMENTATION OF SIX SIGMA IN THE MANUFACTURING INDUSTRY OF THE PHILIPPINES - Catalino N. Mendoza; Leila M. Valero (Journals Park Publishing, 2022)
The study focuses on the baseline implementation of Six Sigma in the Select Manufacturing Industry of the Philippines using quasi-experimental approach. Of which found out that the following are the factors that contributed to the effectiveness of Six Sigma: Defect/error reduction, Customer satisfaction, Cost reduction and Better employee efficiency and found out that there are significant effects on the factors that contributed to the effectiveness of baseline implementation process using Six Sigma Methodology. Based on these factors, a project selection criterion for Six Sigma projects should be established of which the intensive support of the top management people is very essential in the establishment of total quality management eventually maximizing profitability.
Keywords: Baseline; Six Sigma; Effective Process